Difference Pattern Synthesis Based on Superposition Principle - Qi, Yang-Xiao; Li, Jian-Ying (IEEE transactions on antennas and propagation, 2021)
The generation process of difference beam is analyzed from the perspective of beam superposition. By analyzing the continuous linear source, a differential beam synthesis method, which can control the sidelobes level, is proposed with a simple form. The sidelobes level of the difference pattern is determined by controlling the direction of the subbeam and applying the traditional synthesis method, such as Chebyshev method and Taylor method. The proposed synthesis method is theoretical and explicit. Examples are presented for assessing the capabilities of the synthesis of difference patterns. The general distribution function is given.